Are the outcomes of Japanese pancreas transplantation utilizing extended‐criteria donors acceptable? A propensity score matching analysis for donors <50 or ≥50 years old. (31st May 2020) - Ito, Taihei; Kenmochi, Takashi; Aida, Naohiro; Kurihara, Kei; Asaoka, Tadafumi; Ito, Toshinori
Summary: In Japan, about 30% of pancreatic transplant donors are ≥50 years old, making them "extended‐criteria donors (ECDs)." We analyzed 361 cases of transplantation involving donors from the Japanese pancreas transplantation registry to evaluate the acceptability of ECDs. The patient survival rates at 1, 5, and 10 years after transplantation were 96.6%, 94.9%, and 88.3%, respectively. The survival rates of pancreas and kidney grafts at 1, 5, and 10 years were 85.3%, 74.8%, and 70.6%, and 94.2%, 90.9%, and 80.9%, respectively. Multivariate analysis revealed that no particular donor factors significantly influenced the pancreatic graft survival. Patients were divided into 2 groups: donors ≥50 years old (older group) and those <50 years old (younger group). After propensity score matching, the overall pancreatic graft survival at 1, 5, and 10 years after transplantation in the older group was 82.8%, 71.8%, and 69.5%, respectively, which was almost the same as in the younger group (84.9%, 70.2%, and 67.4%, respectively). No donor factors markedly influenced the pancreatic graft survival, and the outcomes of pancreas transplantation from ECDs ≥50 years old were comparable to those from younger donors.